Pengaruh Tabungan Mudharabah dan Deposito Mudharabah Terhadap Produk Domestik Bruto di Indonesia - Ayu Nisrina Indah Sari (Jurnal Manajemen Bisnis Performa, 2023)
Investment has an important role in the Gross Domestic Product component of expenditure. In this study, the author took the independent variables of savings and mudharabah deposits in influencing Gross Domestic Product. The agreement used in this study is mudharabah. Researchers use secondary data for quantitative research. Based on partial and simultaneous tests, each independent variable consisting of savings and mudharabah deposits has an effect on GDP (dependent variable). Multicollinearity test in this study all variables indicated multicollinearity. Based on the T test and F test, there is relevance between the results of statistical tests and economic theory, which is a component of gross domestic product expenditure.